PERAN SERIKAT PEKERJA DALAM PROSES PENENTUAN UPAH MINIMUM (UMK) DI KOTA BEKASI TAHUN 2015 - suci meyta wati; yuwanto .; muhammad adnan (Journal of Politic and Government Studies, 2016)
AbstractWages are an important component in employment, that as one element in the implementation ofthe employment relationship, which has a strategic role in the implementation of industrialrelations, basically should be proportional to the contributions already made workers / laborers inproducing goods or services. But wages are felt by laborers / workers is still lacking to meet theneeds of decent living. Therefore, the problem in this research is "What is the role of tradeunions in the process of determining the minimum wage for Bekasi City," and "Factorssupporting and inhibiting the role of unions in wage determination".This study aims to determine the role of trade unions in determining the minimum wageBekasi City, and also look at the factors supporting and inhibiting factors that become obstaclesin the minimum wage. The research method used is descriptive qualitative primary data obtainedthrough interviews and secondary data from documents, or records, and other sources associatedwith the research. Analysis techniques used by the author uses data qualitative analysis in theform of illustration and description are also drawing conclusions on the symptoms studied.From the research, suggests that the role of trade unions is to join the Wages Council andis actively involved in the process of determining the minimum wage by providing considered aswell as the proposal on the minimum wage increase during the talks. As a member WageCouncil, is a trade union into a single entity on behalf of the union / labor. Therefore, the role oftrade unions is considered essential to the aspirations of the workers, especially in thedetermination of wage negotiations, which reflects that the union managed to raise the minimumwage. It can be concluded that trade unions play a role despite not reaching the initial proposal inthe amount of 3.1 million and a minimum wage for 2015 already in the set in accordance withthe decree of the Governor of West Java Letter No. 560 / Kep.1581-Bangsos / 2014.Advice can be given, among others As a member of the Remuneration Council Bekasi,trade unions should conduct a survey in accordance with the Regulation of the Minister ofLabour that have been listed in the Components and Implementation Phases Achievement NeedsLife, This is because when the survey is carried out not in accordance with existing regulations,unions to be able to utilize and give wisdom to face and overcome the obstacles that exist withinthe union as well as the barriers that exist outside the union,Keywords: Role of Trade Unions Bekasi, Wage Determination Process